Adaptation of Biscay model in Indonesian tax reform: SDGs-based fiscal incentive innovation to realize sustainable economic transformation towards golden Indonesia 2045 - Muhammad Adnan Nurcahyo; Dewinta Iga Wardani (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: The vision of a Golden Indonesia 2045 is a great goal of Indonesia in celebrating its 100 years of independence, but a number of challenges such as demographic bonus, climate change, and economic problems can be obstacles to its achievement. Facing these challenges, the government can implement Sustainable Development Goals (SDGs), in which case, the Biscay Model is one of the evolutions in the field of taxation that can help the development of SDGs implementation in Indonesia. Spain's macroeconomic indicators show positive prospects, characterized by GNI per capita growth increasing from 1.2% in 2019 to 2.7% in 2023, as well as FDI net inflows rising from USD 10.47 billion in 2019 to 19.92 billion in 2024. Methods: This research uses a qualitative method with a literature study approach to examine the opportunity to apply the Biscay Model in the Indonesian tax system as an instrument that supports the achievement of sustainable development goals. Findings: The results show that the Biscay Model has the potential to be applied in Indonesia because it can open up space for the private sector to play an active role in financing development, strengthen government and business collaboration, and accelerate the achievement of the Golden Indonesia Vision 2045. Conclusion: Thus, this model not only presents an innovative alternative fiscal strategy, but also an important opportunity to promote economic, social and environmental sustainability. Novelty/Originality of this article: The novelty of this research lies in assessing the direct connection between the SDGs-based taxation model and Indonesia's long-term development vision, thus offering a new perspective on the role of taxation in supporting sustainable transformation.